The clinical effect of β-elemene-assisted radiochemotherapy in the treatment of esophageal cancer: a systematic review and meta-analysis - Li, Chenxi; Zeng, Yiying; Zhang, Nana; Zhai, Bingtao; Zhang, Chao; Zhu, Yao; Zeng, Zhaowu; Xie, Tian (Translational Cancer Research, 2018)
Background: The involvement of traditional Chinese medicine β-elemene in the treatment of esophageal cancer with radiochemotherapy could make a difference on clinical outcomes.This meta-analysis was conducted to analyze the safety and efficacy of helpful role with β-elemene in assisting the treatment of radiochemotherapy. Methods: Literature retrieval was performed in Chinese Journal Full-text Database, Wanfang Database, China Biological Science Literature Database, VIP Knowledge Resource System, Web of Science, PubMed and assisted in other searches. Randomized controlled trials (RCTs) to evaluate effects of β-elemene-assisted radiochemotherapy for EC were identified. Data extracted from documents that meet the inclusion criteria we defined. Review Manager 5.3 (RevMan5.3) was used for data analysis. Results: A total of 14 studies were included with 1,034 individuals. The results of Meta-analysis indicated that the esophageal cancer (EC) patients received β-elemene adjuvant therapy were superior to the control group in improving the response rate [odds radio (OR) =0.14, 95% confidence intervals (CIs): 0.09–0.19, P